(untitled) (Journal of the College of Basic Education, 2022)
This research aims , to reveal representations of violence in the Arabnevel feminism , hastakaken the researcher from the novel" No Longer " by Saudi novelist "ZainabHanafi "Amodel for her . The research was under taken to stand at the concept of violence in language and idiom , then we study the most important types of violence and then monitorthe most important narrative passages that embody violence , thenovel in her novel deals with violence or all kinds , especially social violenc.